Islamic Religious Education in the Formation of Moral and Religious Values: Pendidikan Agama Islam dalam Pembentukan Moral dan Nilai Keagamaan - Nur Aziza; Ermis Suryana; Zulhijra (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to analyse the role of Islamic Religious Education (IRE) in shaping the religious and tolerant character of students through a literature review approach. In the context of a multicultural society and the digital age, religious values and tolerance are important elements in character education. Based on a review of several literature sources (Arifim 2020, Rizkia and Zaedi 2019, Bangun and Ndoana 2024, Putra and Fauzi 2024 dan Aviatin, Robandi, and Komalasari 2023), it was found that PAI plays a strategic role in instilling values of faith, worship, and morality through value-based learning, teacher role modelling, digital media, and intercultural dialogue. These strategies have proven effective in fostering inclusive religious character and a tolerant attitude toward diversity. This article recommends strengthening the PAI curriculum with a reflective and contextual approach to support the development of students who are not only religiously devout but also capable of living harmoniously in a pluralistic societyHighlight : Islamic Religious Education fosters religious and tolerant character through value-based learning and role modelling. Digital media and intercultural dialogue enhance students' understanding and empathy in a diverse society. A holistic, reflective, and contextual curriculum strengthens spiritual values and social harmony. Keywords : Islamic Religious Education, Religious Character, Tolerance, Digital Media, Teacher Role